Flipbook trends and their influence on the development of guidance and counseling teaching media in higher education: Bibliometric analysis - Imam Ariffudin; Leny Latifah (Journal of Advanced Guidance and Counseling, 2022)
Purpose – The purpose of this research is to map relevant topics that support the renewal of research topics on the development of flipbook-based media.Method – A bibliometric study using Zupic and Carter models was chosen as the basis for conducting the research. The research data were 1387 articles indexed by Scopus and Google Scholar which were filtered using the Publis or Perish. The compiled article data was then analyzed using VOSviewer to identify visualizations.Result - The results show that e-module is the most widely used teaching material for flipbooks, while interactive flipbooks and e-worksheets are alternative topics in the development of flipbook media.Implication – This study suggests that educators in tertiary institutions or future researchers are more innovative and varied in developing learning resources and learning media.Originality – this research is the first study that tries to discuss the novelty of the flipbook research topic.***Tujuan – Tujuan penelitian ini adalah untuk memetakan topik-topik yang relevan yang mendukung pembaharuan topik penelitian tentang pengembangan media berbasis flipbook.Metode - Studi bibliometrik dengan menggunakan model Zupic dan Carter dipilih sebagai dasar pelaksanaan penelitian. Data penelitian berupa 1387 artikel yang terindeks Scopus dan Google Scholar yang disaring menggunakan perangkat lunak Publis or Perish. Data artikel yang terkumpul kemudian dianalisis menggunakan VOSviewer untuk mengidentifikasi visualisasi.Hasil - Hasil penelitian menunjukkan bahwa e-modul merupakan bahan ajar yang paling banyak digunakan untuk flipbook, sedangkan flipbook interaktif dan e-worksheet menjadi topik alternatif dalam pengembangan media flipbook.Implikasi - Penelitian ini menyarankan agar para pendidik di perguruan tinggi atau peneliti selanjutnya lebih inovatif dan variatif dalam mengembangkan sumber belajar dan media pembelajaran.Orisinalitas - Penelitian ini merupakan penelitian pertama yang mencoba membahas kebaruan topik penelitian flipbook.